Prospective clinical trial examining the impact of genetic variation in FADS1 on the metabolism of linoleic acid– and ɣ-linolenic acid–containing botanical oils. Issue 5 (13th March 2020) - Sergeant, Susan; Hallmark, Brian; Mathias, Rasika A; Mustin, Tammy L; Ivester, Priscilla; Bohannon, Maggie L; Ruczinski, Ingo; Johnstone, Laurel; Seeds, Michael C; Chilton, Floyd H
ABSTRACT: Background: Unexplained heterogeneity in clinical trials has resulted in questions regarding the effectiveness of ɣ-linolenic acid (GLA)-containing botanical oil supplements. This heterogeneity may be explained by genetic variation within the fatty acid desaturase ( FADS ) gene cluster that is associated with circulating and tissue concentrations of arachidonic acid (ARA) and dihomo-ɣ-linolenic acid (DGLA), both of which may be synthesized from GLA and result in proinflammatory and anti-inflammatory metabolites, respectively. Objectives: The objective of this study was to prospectively compare the capacity of a non-Hispanic white cohort, stratified by FADS genotype at the key single-nucleotide polymorphism (SNP) rs174537, to metabolize 18-carbon omega-6 (n-6) PUFAs in borage oil (BO) and soybean oil (SO) to GLA, DGLA, and ARA. Methods: Healthy adults ( n  = 64) participated in a randomized, double-blind, crossover intervention. Individuals received encapsulated BO ( Borago officinalis L.; 37% LA and 23% GLA) or SO [ Glycine max (L.) Merr.; 50% LA and 0% GLA] for 4 wk, followed by an 8-wk washout period, before consuming the opposite oil for 4 wk. Serum lipids and markers of inflammation (C-reactive protein) were assessed for both oil types at baseline and during weeks 2 and 4 of the intervention. Results: SO supplementation failed to alter circulating concentrations of any n-6 long-chain PUFAs. In contrast, a modest daily dose of BO elevated serum concentrations of GLA and DGLA in an rs174537 genotype–dependent manner. In particular, DGLA increased by 57% (95% CI: 0.38, 0.79) in GG genotype individuals, but by 141% (95% CI: 1.03, 2.85) in TT individuals. For ARA, baseline concentrations varied substantially by genotype and increased modestly with BO supplementation, suggesting a key role for FADS variation in the balance of DGLA and ARA. Conclusions: The results of this study clearly suggest that personalized and population-based approaches considering FADS genetic variation may be necessary to optimize the design of future clinical studies with GLA-containing oils. This trial was registered at clinicaltrials.gov as NCT02337231.